Improve critical thinking skills using traditional musical instruments in science learning - Anggi Datiatur Rahmat; Heru Kuswanto; Insih Wilujeng; Elisabeth Pratidhina (Institute of Advanced Engineering and Science, 2023)
Experiment activity is an essential part of science learning. Suling (flute), a traditional musical instrument from West Java, can be used as a learning media for sound wave concepts. Technology-based mobile can be used as an experimental tool is Phypox. This study aims to report using a combination of Suling and Phypox in experiment activities. The designed activity aims to engage students in critical thinking. The instrument for measuring critical thinking consists of five questions based on the critical thinking aspect: interpretation, analysis, evaluation, inference, and explanation. The study used a one-group pre-and post-test design on 32 8th-grade students at one of the junior high schools in West Java Province, Indonesia. The study procedure is a pre-test, discussion of Suling’s concepts, introduction to Phypox application, experiment activity, presentation, and post-test. Data analysis uses the normalized gain to compare the pre-and post-test. Experiment activities help students to understand frequency, open organ pipes concepts, and investigate the speed of sound produced by Suling. The study found a significant change in the pre-and post-test scores of students after experimenting, so it could be interpreted that the experimental activities using Suling and Phypox affected critical-thinking students.